Data envelopment analysis technique to measure the management ability: Evidence from Iran Cement industry - Akbar Valizadeh Oghani; Farzin Modarres Khiyabani; Nasser Fegh-Hi Farahmand (Cogent Business & Management, 2020)
The purpose of this study is to measure the ability of management within the cement industry with a new pattern that has been a member of the Iranian stock exchange. With regard to this matter, the data of companies' financial statements from 2012 to 2016 were used. First, by implementing a suitable model and regional data envelopment analysis model, relative efficiency for each of the companies was calculated and the capable units have been ranking by Anderson-Peterson method as well, then a regression model was estimated. The indexes of company management abilities were calculated. To evaluate the relative efficiency optimization software GAMS and to determine the ability of management software E-Views were used. Our purpose was to achieve the non-inherent ability of managers in units. The result of the research shows that the efficiency or inefficiency of the companies can be related to the inherent and acquired ability of managers. The results indicate that companies that have been evaluated with a score productively, don't simply guarantee of the elevated ability of their managers (for example, Iran Chalk Co. & Ardabil Cement Co.). The ability of some companies' managers who have been Efficiently evaluated was also high (for example, Khuzestan Cement Co. & Mazandaran Cement Co.).
Keywords: 650; Cement industry; relative efficiency; management ability; data envelopment analysis